How the recruitment process of Green Delta Securities Limited overcame challenges and achieved results during Covid 19 - Maliha, Ramisha (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.